A Hesitant Fuzzy Set Approach to Ideal Theory in Γ-Semigroups. (2nd September 2018) - Abbasi, Mohammad Y.; Talee, Aakif F.; Khan, Sabahat A.; Hila, Kostaq
Abstract : We apply the hesitant fuzzy sets theory to Γ -semigroups and provide some characterizations of hesitant fuzzy left (right and bi-) ideals. We introduce the hesitant fuzzy left (resp., right and two-sided) ideal, hesitant fuzzy bi-ideal, and hesitant fuzzy interior ideal in Γ -semigroup and study some properties of them. Finally, a characterization of a simple Γ -semigroup by means of a hesitant fuzzy simple Γ -semigroup is obtained.